Ultrasonic sculpting of virtual optical waveguides in tissue - Maysamreza Chamanzar (Nature Portfolio, 2019)
Optical imaging of tissue is a powerful technique but delivering light deep into scattering tissue is not possible without using invasive methods. Here, the authors demonstrate that patterned ultrasound can define and control the trajectory of light in tissue using pressure-induced index contrasts.